KESETARAAN GENDER MENURUT AMINA WADUD: Penafsiran Kontekstual Dalam Al-Qur'an - Aji Febriansyah; Aldi Armansah Prayoga; Siti Maysaroh (Almustofa Journal of Islamic Studies and Research, 2025)
Women have a noble position in the Qur'an, where many verses explicitly discuss their rights and roles. However, in social practice, women are often undervalued and placed below men. One of the reasons for this is the gender-biased construction of classical tafsir, which limits the interpretation of Qur'anic verses and reinforces patriarchal norms. Criticism of this interpretation model has emerged from various circles, especially Muslim feminists, including Amina Wadud. Through a contextual hermeneutic approach, Wadud offers a new reading of Qur'anic texts that are considered to limit the role of women. By considering linguistic, historical, and socio-cultural aspects at the time of revelation, she seeks to deconstruct patriarchal interpretations and build a more gender-equitable understanding. This research aims to explore Wadud's contribution in creating space for women in religious contexts and encouraging more inclusive social change, where gender equality can be realized. The results are expected to provide new insights in understanding the role of women in Islam and encourage more constructive dialogue on gender issues in society.